Daftar Isi Jurnal Muara Ilmu Sosial, Humaniora, dan Seni Vol 2 No 1 - DPPM UNTAR (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2018)
Daftar Isi Jurnal Muara Ilmu Sosial, Humaniora, dan Seni Vol 2 No 1